A Nurse Theorist's Life of Providence: A Dialogue With Sister Callista Roy. - Morrow, Mary R.; Roy, Callista (Nursing Science Quarterly, 2022)
The year 2022 is Nursing Science Quarterly 's 35th year in publication, and we are dialoging with nurse theorists. We hope to uncover influences and origins of their theoretical thinking and hear about their current projects related to nursing science. In this scholarly dialogue column, we dialogue with Sister Callista Roy, nurse theorist, retired professor at Mount Saint Mary's University and Professor Emeritus at Boston College Connell School of Nursing. Her contribution to nursing science began in her master's program and her Roy adaptation model (RAM) has been the foundation for countless studies across at least five continents, nursing programs, and implementation practice projects.